Cladistic Analysis of Morpho-anatomical Data of Subtribe Coelogyninae of Nepal Himalaya - Bajracharya, Devendra Mananda; Dongol, Gita; Rajbhandary, Sangeeta (Journal of Plant Resources, 2022)
A cladistic analysis of subtribe Coelogyninae based on 10 morphological and 19 anatomical characters of 20 species of Coleogynae, Pholidota, Panisea and Pleione from Nepal was done. Most parsimonious tree were traced using computer assisted software NONA, Winclada (123 trees with CI = 35 and RI = 57). The analysis confirms the monophyletic origin of the subtribe Coelogyninae and species assorted into two different clades. Clade I is separated by round to oval mesophyll cell shape, such as in the species of Otochilus, Panisea and Pleione. Whereas the clade II is separated by stomatal index value 10-15. The results of cladistic analysis suggest that the subtribe Coelogyninae is monophyletic.